CONSTRUCTION OF NATIONALISM ON PAPUAN COLLEGE STUDENT IN SURABAYA IN MULTICUTURALISM PERSPECTIVE - Darsono Darsono (JOURNAL OF LAW AND GOVERNMENT SCIENCE, 2015)
This research is motivated by the upsurge of inter-ethnic tensions in Indonesia relations, the demands of ethnic independence, double nationalism of Papuans, and various activities of Papuan college students who come into contact with leading political and cultural demands for independence. The focuses of myresearch is (1) essential-primordial elements are constructed, (2) the factors that influence the development of Papuan nationalism construction, (3) the construction process Papuan nationalism, and (4) the meaning of nationalism Papua on Papuan college students in Surabaya in the perspective of multiculturalism.To examine these focuses, Iused the theory of constructive nationalism multiculturalism perspective. Following theorists of nationalism constructive thoughts Hobsbawm (1990) with "invented tradition", Anderson (1983) "imagined political community", Gellner (1983; 1987; 1994) "fabrication as true community", and Kedourie (1993) "nationalism as a movement "social entities and social identity as a people (nation) is something that is constructed. These theories used in the perspective of multiculturalism Parekh (2000) that promote cross-cultural dialogue on the basis of cultural diversity, that coexistence is not only principled, but pro-existence. Structuralism theory by de Saussure and post-structural of Barthes and deconstruction of Derrida, and as well as post-colonial Orientalism of  Said (1978) was also used.  As a form of qualitative research with the social definition paradigm, this research uses ethnographic approach (Fetterman, 2010) with the emic-ethic perspective. By taking location in Surabaya, data were collected from 35college students from Papua with observation techniques, in-depth interviews either directly, by phone, or e-mail, focus of group discussion (FGD), and surf the internet, the blogs, facebooks, and twitter are related to their activity.The resulting findings can be summarized as follows. Consciousness as a nation and a stronger Papuan nationalism is constructed on the essential elements of the primordial. This construction is influenced by various factors, namely awareness of students as agents of change, colonization by mass transmigration process, the exploitation of natural resources, marginalization of indigenous Papuans, and the violence and human rights violations. Papuan nationalism construction proceeds through the development of Papuan college student organization that later became the pioneer rejection of government programs, international contacts, and demands for independence. Papuan nationalism is as a meaningful cultural reorientation and development of modern Papua.Keywords: Papuan nationalism, multiculturalism,Papuan college students, construction, reorientation of political-cultural, multicultural-nationalism-constructive